Participation of Kazakhstan Pharmaceutical Companies in Global Value Chains - Frolova, Elena D.; Abdurahkmanova, Zulparuza A.; Ishukov, Alexander A. (Economy of Regions, 2021)
Growing interest of national economies in global value chains (GVCs) and the lack of micro-level research brought us to study the integration of countries in GVCs at the enterprise level (using the example of the pharmaceutical industry). We examine the situation in the Republic of Kazakhstan that is beginning to integrate into GVCs. Results of a questionnaire survey of the country’s pharmaceutical companies are considered along with public statistics. We developed a methodology to analyse the participation of a national entity in GVCs at the micro-level (including the enterprise participation in GVCs) and assess the performance of Kazakh pharmaceutical companies. The research is based on export and import data. A hypothesis on the participation of national pharmaceutical enterprises was partially confirmed: several surveyed companies participate in generic drugs GVCs at the production level, thus the value added is low. Features of pioneering entry into pharmaceutical global value chains for countries lacking such integration experience were demonstrated on a specific example. The obtained results can be used by countries starting the process of integration into pharmaceutical GVCs, as well as by Kazakhstan when developing the pharmaceutical industry.